A Review On Literatures Of Islamic Financial Institutions And Market Between 2010 – 2020 - Muhammad Ridhwan Ab. Aziz; Nur Syazwani Binti Khalid; Maryam Husna Binti Ahmad Firdaus; Anis Farita binti Muhamad Yatim; Fakilah Anurul binti Mohd Azli Navamohan; Muhammad Nur Wafi bin Omar (University of Nebraska, 2024)
Indexed by SCOPUS/ERA